Striking a Balance: Modulation of Host Cell Death Pathways by Legionella Pneumophila - Luo, Zhao-Qing (Frontiers in Microbiology, 2011)
Programmed cell death is considered the ultimate solution for the host to eliminate infected cells, leading to the abolishment of the niche for microbial replication and the ablation of infection. Thus, it is not surprising that successful pathogens have evolved diverse strategies to reprogram the cell death pathways for their proliferation. Using effector proteins translocated by the Dot/Icm type IV secretion system, the facultative intracellular pathogen Legionella pneumophila manipulates multiple host cellular processes to create a niche within host cells to support its replication. Investigation in the past decade has established that in mammalian cells this bacterium actively modulates two host cell death pathways, namely the canonical apoptotic pathway controlled by the mitochondrion and the pyroptotic pathway controlled by the Nod-like receptor Naip5 and the Ipaf inflammasome. In this review, I will discuss the recent progress in understanding the mechanisms the bacterium employs to interfere with these host cell death pathways and how such modulation contribute to the intracellular life cycle of the pathogen.